FXII (46C→T) Polymorphism and In Vivo Generation of FXII Activity - Kohler, H. P.; Futers, T. S.; Grant, P. J. (Thrombosis and Haemostasis, 1999)
Increased Factor XIIa concentrations have been found in association with coronary artery disease. Recently, a common 46 C to T point mutation in exon 1 of the factor XII gene has been described which is associated with lower FXII clotting activity and lower zymogen levels in relation to possession of the T allele. It is not known whether this polymorphism relates to the phenotypes of FXIIa in vivo or to coronary artery disease. The aim of the study was to investigate the interaction of this polymorphism with FXIIa plasma levels and to study the prevalence of the polymorphism in 266 patients with suspected coronary artery disease characterised by angiography and in 185 healthy controls. FXIIa levels were strongly associated with FXII genotype with lower levels with increasing numbers of T alleles (p <0.0001). There was no difference between the prevalence of this polymorphism in patients with MI compared to those without MI and controls and between all patients and controls (p ≥0.2, chi-square test). There was no association between extent of coronary artery disease (0, 1, 2, and 3 vessel disease) and FXII genotype. In conclusion, the common 46 C to T point mutation is strongly associated with FXIIa but the present study did not show an association with coronary artery disease. The role of this polymorphism in other thrombotic disorders such as ischemic stroke and venous thrombosis and its clinical significance in FXII deficient states remains to be investigated.